2009
DOI: 10.1037/a0014240
|View full text |Cite
|
Sign up to set email alerts
|

Early gender differences in self-regulation and academic achievement.

Abstract: This study examined gender differences in self-regulation in the fall and spring of kindergarten and their connection to gender differences in 5 areas of early achievement: applied problems (math), general knowledge, letter-word identification, expressive vocabulary, and sound awareness. Behavioral selfregulation was measured using both an objective direct measure (N ϭ 268; Head-Toes-Knees-Shoulders task) and, for a subsample of children, a teacher report of classroom self-regulatory behavior (n ϭ 156; Child B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
386
7
31

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 568 publications
(483 citation statements)
references
References 83 publications
59
386
7
31
Order By: Relevance
“…An analysis of the studies suggests that gender differences in self-regulation remain a rather controversial issue that needs to be studied. On the one hand, it is shown that in the preschool age and in primary http://dx.doi.org/10.15405/epsbs.2017.12.11 Corresponding Author: Tatiana Fomina Selection and peer-review under : 2357-1330 108 school girls outperform boys in certain features of self-regulation (Matthews, Ponitz & Morrison, 2009;Zimmerman & Martinez-Pons, 2009). On the other hand, in the older school age, these differences become minimal.…”
Section: Resultsmentioning
confidence: 99%
“…An analysis of the studies suggests that gender differences in self-regulation remain a rather controversial issue that needs to be studied. On the one hand, it is shown that in the preschool age and in primary http://dx.doi.org/10.15405/epsbs.2017.12.11 Corresponding Author: Tatiana Fomina Selection and peer-review under : 2357-1330 108 school girls outperform boys in certain features of self-regulation (Matthews, Ponitz & Morrison, 2009;Zimmerman & Martinez-Pons, 2009). On the other hand, in the older school age, these differences become minimal.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that observer bias in the teacher measures of self-regulated learning has been documented recently in the literature (Matthews et al 2009), appreciating that these biases may have affected the results presented in this study seems appropriate. Even further, as teachers' post-test questionnaire responses were retrospective, it is possible that post-test results may have included their perceptions of the results of their implementation of the CREST programme (Rozendaal et al 2005).…”
Section: Methodological Considerations and Future Researchmentioning
confidence: 94%
“…In order to address the first research question, one-way ANOVAs were run on all pre-test scores to investigate any differences between groups at the outset of the study. Repeated measures ANOVAs were avoided as the F test for treatment main effect is too conservative as pre-test scores are not affected by the intervention (Dimitrov and Rumrill 2003;Matthews et al 2009). Therefore, following the suggestions of Dimitrov and Rumrill (2003) as well as Bonate (2000), one-way ANOVAs using the change scores of student and teacher self-reports while controlling for pre-test academic performance were conducted in order to address the remaining research questions of this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations